Strategic Management of Akad Salam and Istishna in e-Commerce Transactions: A Case Study of Unit-business Pesantren - Manik, M. Rikwan ES.; Asmuni, Asmuni; Anggraini, Tuti (Institut Agama Islam Negeri Lhokseumawe, 2023)
Abstract: This study aims to investigate the e-commerce transaction management models of Akad Salam and Istishna in Pesantren (Islamic boarding institutions). Additionally, the study identifies challenges and opportunities within Pesantren organizations. It investigates Pesantren's potential to utilize e-commerce as a business unit facilitator. The research employs a qualitative methodology and a case study design. The five information sources consist of Pesantren leaders, coordinators of Pesantren business units, Pesantren treasurers, and the secretariat team. The findings suggest that Pesantren have a significant opportunity to leverage e-commerce for transactions based on the Akad Salam and Istishna principles. However, obstacles and the need for public education regarding these principles must be overcome. For the successful implementation of Akad Salam and Istishna in Pesantren e-commerce transactions, awareness, a precise understanding of legal and Shariah aspects, and the implementation of the appropriate technology are crucial. Pesantren must implement a comprehensive and unified strategy for managing Akad Salam and Istishna in e-commerce transactions in order to surmount these obstacles and capitalize on these opportunities. Abstrak: Tujuan penelitian untuk mengetahui model manajemen Akad Salam dan Istishna dalam Transaksi e-Commerce di Pesantren. Selain itu, penelitian ini juga mengidentifikasi tantangan dan Peluang pada Organisasi Pesantren. Penelitian ini menggali potensi pesantren dalam memanfaatkan e-commerce sebagai fasilitator penunjang unit usaha pesantren. Pendekatan ini berjenis kualitatif dengan teknik studi kasus. Sumber informan berjumlah lima orang yang terdiri dari pimpinan pesantren, koordinator unit usaha pesantren, bendahara pesantren dan tim kesekretariatan pesantren. Hasil penelitian menunjukkan Pesantren memiliki potensi yang besar untuk memanfaatkan e-commerce dalam transaksi berbasis akad Salam dan Istishna. Namun, tantangan dan kebutuhan pendidikan masyarakat terkait prinsip-prinsip tersebut harus diatasi. Kesadaran, pemahaman hukum dan syariah yang tepat, serta penerapan teknologi yang tepat menjadi faktor penting dalam keberhasilan implementasi akad Salam dan Istishna dalam transaksi e-commerce di pesantren. Dalam rangka mengatasi tantangan dan memanfaatkan peluang tersebut, pendekatan yang komprehensif dan terintegrasi dalam manajemen akad Salam dan Istishna dalam transaksi e-commerce di pesantren perlu diterapkan.